Cognitive competence: comparing learning between traditional classroom and active classroom - Cotta, Rosângela Minardi Mitre; Ferreira, Emily de Souza; Do Prado, Rogério Elias Gomes; Cavalier, Samantha Bicalho de Oliveira; Da Costa, Glauce Dias; Moreira, Tiago Ricardo (Revista Internacional de Educação e Saúde, 2022)
INTRODUCTION: The new student profile has required new formats of teaching and learning, with interconnected knowledge based on a pedagogical practice founded on reflection OBJECTIVE: The aim of this study was to analyze how students evaluate what they learned using the of the Concept Map associated with the Inverted Classroom in the teaching, learning and assessment process compared to the Traditional Classroom. METHODS AND MATERIALS: A cross-sectional study carried out with 90 students at a public university in Brazil in the years of 2016 to 2018. For data collection the authors used a high reliability tool based on the Likert scale of 4 points containing questions regarding the competences to be developed by the students. The Kolmogorov-Smirnov normality test was performed and the Wilcoxon test was used to identify the differences between the two methods. The level of significance was 5%. RESULTS: The mean attributed to each of the two investigated methods was significantly higher (p <0.001) in the Concept Map with Flipped Classroom (3.38) than in the Traditional Classroom (2.75). CONCLUSIONS: While the Concept Map favors the process of meaningful learning with comprehension, integration and assimilation of content in an autonomous and co-responsible form by the students, the Traditional Classroom is based on the passive memorization of the content given by the teachers. Because of this, it is suggested that, the Concept Map with a Flipped Classroom according to the perception of the students was more effective when compared to the Traditional Classroom, by providing the assimilation, interpretation and integration of the contents.